Drivers of coastal dune dynamics on the Younghusband Peninsula, South Australia = Fatores controladores da dinâmica de dunas costeiras na Península de Younghusband, Austrália do Sul - Moulton, Martim Almeida Braga (2023)
Coastal dune development and evolution has been one of the main research topics in coastal science (Martínez and Psuty, 2004). However, due to the complexity of the interactions between different driving factors that dictate coastal dune dynamics, the roles that each of the abiotic and biotic drivers play in formation and transformation of these deposits are still poorly understood (Provoost et al., 2011; Barchyn and Hugenholtz, 2012). In a historical time-scale (years to decades) dunefields can undergo significant morphological and ecological changes, shifting from an active/unvegetated state to a stabilized/vegetated state, and vice versa (Hesp, 2013). Studying how dunes evolve in a meso-scale analysis poses a significant challenge to researchers because of the difficulty in combining or obtaining spatial data with enough resolution over a significant period of time (Pickart and Hesp, 2019), and therefore studies that show medium to long-term dune changes are scarce (Hesp, 2013). In the Younghusband Peninsula dune system (South-east coast of South Australia), the availability of high-resolution historical spatial data, combined with climatic data, oceanographic data, and specific environmental conditions, constitutes a good opportunity to study different aspects of meso-scale morphological changes and their main driving factors. The objective of this body of work is to examine the different aspects of meso-scale driving factors of coastal dune dynamics, with the Younghusband Peninsula (YP) as a study case. This work investigates specifically: (1) What were the potential drivers of vegetation cover changes in the last ~70 years; (2) What were the geomorphological changes that occurred due to this vegetation cover vi changes and how did this morphological evolution take place; and (3) What are the main drivers that dictate the foredune morphological variability identified in the southern portion of the YP. The first part of this study (published in Earth Surface Processes and Landforms Journal – Moulton et al., 2019) uses historical aerial images and data from potential biotic and abiotic drivers to investigate why vegetation cover has changed in the last ~70 years in the northern YP. Results show that the decline in exotic rabbit abundance, especially in the 1950s after the introduction of the Myxomatosis virus, present significant correlation to periods of greater vegetation growth. Other factors, such as wind and precipitation variability, did not present any explanatory correlation, leading to the conclusion that rabbit grazing was the most important driving factor of vegetation growth in the YP during this period. The second part of this study investigates the geomorphological transformations induced by the vegetation changes and how the evolution of different dune types took place, with the use of historical aerial imagery and three-dimensional high-resolution topographic data. From 1949 to 2018, the dune system went through significant geomorphological changes due to vegetation stabilization, with relatively simple active transgressive dunefields changing into a complex landscape of active and vegetated blowout/parabolic dunes. Vegetation growth on the marginal interdune depressions and plains, forming narrow elongate vegetated ridges was the main process that lead to the development of a complex of blowouts and parabolic dunes, most of which are already stabilized by 2018. The third and final part of this study investigates the role of various factors controlling foredune evolution that accounts for the alongshore geomorphological vii and volumetric differences along the southeastern portion of the Younghusband Peninsula. For this study a 16 km stretch of beach on the barrier was selected, where minimal environmental changes in some factors such as wind energy and aeolian transport occur. Results show a south to north alongshore increase in foredune height and volume for the 3 years surveyed, together with an increase in wave energy, while other driving factors showed minimal to no changes. These findings indicate that wave energy has an indirect positive relationship with foredune accretion, with wave driven sediment supply to the beach increasing as wave energy rises from south to north. In this study area wave energy has more significant role than aeolian transport limitations on foredune (and relict foredune) development.